The Effect Of Numbered Head Together And Motivation In Learning Toward Students’ Speaking Ability - Darmajaya, Lalu Arwan; Saputra, Ari (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to investigate the effect of NHT technique and students’ motivation in learning toward the speaking ability of the twelfth grade students of SMAN 8 Mataram . Designed as an experimental research with posttest-only control group design, it examined a sample of two classes of twelfth grade students of SMAN 8 Mataram. In taking the sample, group random sampling technique was used. Each class was divided into two groups (the students who had high and those who had low motivation). Speaking test and questionnaire of motivation in learning were the instruments which were used to collect the data. Then the data were analyzed by using analysis of multi variance (ANOVA). The result of the analysis indicate that (1) NHT technique is more effective than conventional technique in teaching speaking since Fcount = 35.132 is higher than Ft = 3.970; (2) there is a significant difference in speaking ability between high motivation students who were taught using NHT technique and those who were taught using conventional technique because Fcount (8.090) is higher than Ft (4.113) in 0.05 level of significant; (3) there is significant difference in speaking ability between low motivation students who were taught using NHT technique and those who were taught using conventional technique because Fcount (19.122) is higher than Ft (4.133) in 0.05 level of significance.